Development of microsatellite markers for the soft tick Ornithodoros phacochoerus - (:unkn) unknown (My University, 2024)
Soft ticks of the genus Ornithodoros are responsible for the maintenance and transmission of the African swine fever (ASF) virus in the sylvatic and domestic viral cycles in Southern Africa. They are also the main vectors of the Borrelia species causing relapsing fevers. Currently, no genetic markers are available for Afrotropical Ornithodoros ticks. As ASF spreads globally, such markers are needed to assess the role of ticks in the emergence of new outbreaks. The aim of this study is to design microsatellite markers that could be used for ticks of the Ornithodoros moubata complex, particularly Ornithodoros phacochoerus , to assess population structure and tick movements in ASF endemic areas. Methods A total of 151 markers were designed using the O. moubata and O. porcinus genomes after elimination of repeated sequences in the genomes. All designed markers were tested on O. phacochoerus and O. porcinus DNA to select the best markers. Results A total of 24 microsatellite markers were genotyped on two populations of O. phacochoerus and on individuals from four other Ornithodoros species. Nineteen markers were selected to be as robust as possible for population genetic studies on O. phacochoerus . Conclusions The microsatellite markers developed here represent the first genetic tool to study nidicolous populations of O. phacochoerus . Graphical Abstract
Keywords: African Research